Economic feasibility through the optimal capacity calculation model of an energy storage system connected to solar power generator. Issue 5 (August 2020) - Kang, Min-Su; Park, Young-Kwon; Kim, Kyung-Tae
In this study, the optimal capacity of a battery and power conditioning system (PCS) of energy storage system were calculated. In addition, economic analysis was conducted to determine the optimal equipment standard, taking the government support plan into account. In addition, the changes in the power generation pattern were examined when the energy storage system and photovoltaic (PV) were connected to verify the power peak management efficiency of the energy storage system. Moreover, the effect of the energy storage system support policy was assessed by comparing the economic efficiency of single-PV equipment and energy storage system-connected equipment by the internal rate of return. Internal rate of return was analyzed by the change in cost of energy storage system equipment and the price of system marginal price/renewable energy certificate, which was a sales factor, and used for economic forecasting of the energy storage system. To accomplish this, the 2015 power generation output data (daily average 3.69 h power generation) of LG Hausys Ulsan station were converted to small-scale (3 MW) and large-scale (10 MW) solar power and a model that calculated the factor capacity of battery and the PCS capacity of the energy storage system was then constructed. Furthermore, the selected battery capacity and PCS capacity were analyzed separately by economic analysis to propose an energy storage system equipment standard, which could guarantee the optimal economic efficiency. Finally, based on the "Guideline for Management and Operation of Mandatory Supply for New and Renewable Energy" established by the Ministry of Commerce Industry and Energy, the profit model applied to the economic analysis was limited to an energy storage system charged from 10:00 to 16:00.